If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (209.2)(80 + -1x) = (83.68)(x + -10) (80 * 209.2 + -1x * 209.2) = (83.68)(x + -10) (16736 + -209.2x) = (83.68)(x + -10) Reorder the terms: 16736 + -209.2x = 83.68(-10 + x) 16736 + -209.2x = (-10 * 83.68 + x * 83.68) 16736 + -209.2x = (-836.8 + 83.68x) Solving 16736 + -209.2x = -836.8 + 83.68x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-83.68x' to each side of the equation. 16736 + -209.2x + -83.68x = -836.8 + 83.68x + -83.68x Combine like terms: -209.2x + -83.68x = -292.88x 16736 + -292.88x = -836.8 + 83.68x + -83.68x Combine like terms: 83.68x + -83.68x = 0.00 16736 + -292.88x = -836.8 + 0.00 16736 + -292.88x = -836.8 Add '-16736' to each side of the equation. 16736 + -16736 + -292.88x = -836.8 + -16736 Combine like terms: 16736 + -16736 = 0 0 + -292.88x = -836.8 + -16736 -292.88x = -836.8 + -16736 Combine like terms: -836.8 + -16736 = -17572.8 -292.88x = -17572.8 Divide each side by '-292.88'. x = 60 Simplifying x = 60
| x-2/3x=87 | | 3(y-8)/4=-4y | | 15x+24=139 | | Y=0.0987x+8.1883 | | (x^2d^2-3xd+2i)y=0 | | 1x-3-5x=-27 | | 6x-9x=11x | | 5+6x=4x+10 | | y=0.50x/111 | | 81r^2-5=59 | | 0=3W-8-35 | | 2.5(2)-0.2y=8.1 | | 25x^5-50x^4-x+2=0 | | y=0.50(111)+16 | | x^2-4x-14-x=0 | | 5=7(1)-y | | 7(x-1)+8=5x+2(1+x) | | 14xy-7x+15y-13xy= | | y=-5/6(2)+5 | | -a-3=-2a-3 | | -2/5x-99/10 | | 14y-9-8y-6= | | 6x-10(0)+2=0 | | y=0.50(50)+16 | | 6x-10(2)+2=0 | | 8d-23+d=42 | | y=0.50(100)+16 | | pq-7q+4p-9pq+2q= | | 4x^2+5y^2+16x+10y-79=0 | | 0.6-3.8=0.4 | | 9k+12s-14s+6k-3s= | | -3(t-4)+6t=7t-2 |